Arranging an enantioselective aza-[2,3]-Wittig rearrangement - Davies, Elizabeth Anne (2009)
The use of the aza-[2,3]-Wittig sigmatropic rearrangement in the synthesis of α,α-disubstituted α-amino acids has been investigated with the emphasis on obtaining enantioenriched rearrangement products. It was hoped that an enantioenriched precursor could form an axially chiral enolate which would impart chiral information on the product.